From Literature to Children’s Opera: Fox Moon by Maša Ogrizek as Example of Intermedial Adaptation - Vizjak Puškar, Nika; Forte, Nana (Trideset let literarne nagrade večernica, 2026)
The article discusses the fantasy narrative Fox Moon (2021) by Maša Ogrizek and its opera adaptation (2025) as an example of intermedial transfer of a contemporary youth literary work into a musical-stage medium. The research is based on a qualitative comparative analysis of the literary model, libretto and opera performance and combines a literary, musicological and intermedial approach. The analysis focuses on the organization of space and time, the characterization of characters, motif sets and the role of voice, sound and music. The article shows that the opera preserves the fundamental themes of the literary model, such as growing up, loss, identity and belonging, but transforms them in accordance with the expressive possibilities of the opera medium. Voice, sonority, choir and percussion accompaniment play a particularly important role, co-creating meaning and replacing part of the narrative functions of the literary text. The opera adaptation thus proves to be an independent artistic interpretation, translating literary motifs into the language of sound, rhythm and staging.